PERSEPSI PEGAWAI TERHADAP PENGEMBANGAN KARIR OLEH PIMPINAN BALAI PENDIDIKAN DAN PELATIHAN KEAGAMAAN PADANG - Ghina Imanda (Universitas Negeri Padang, 2017)
The purpose of this research is to get information about employee perceptions of career development by the leader of Padang Islamic Education and training Center. This research is a descriptive study. The population is an employee of Padang Islamic Education and training Center which requires 51 people. The sample was taken as many as 51 people from the total population of less than 100 people. The research instrument is a questionnaire of Likert scale model with five selected answers that have been tested for its validity and reliability. Data were analyzed using the mean score formula. The results show employee perceptions of career mining by the leader of Balai Pendidikan dan Pelatihan Keagamaan Padang in the category enough with the average score achievement score of 3.39.